2019
DOI: 10.3892/mmr.2019.10516
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑34a‑3p inhibits proliferation of rheumatoid arthritis fibroblast‑like synoviocytes

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory joint disease characterized by synovial inflammation. Fibroblast-like synoviocytes (FLS) serve a vital role in the initiation and perpetuation of the immune response in patients with RA. The present study aimed to investigate the potential role of microRNA (miR)-34a-3p in the pathogenesis of RA. FLS were collected from patients with RA and osteoarthritis (OA). The miR-34a-3p mimics and inhibitor vectors were constructed and transfected into RAFLS using Lipofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…MiRNAs have become an important regulator of osteoclastogenesis, osteoblasts growth and differentiation (Chen et al, 2015;Baum and Gravallese, 2016;Liu J. et al, 2019). In experimental arthritis models, miRNAs analogs and antagonists have shown encouraging results as experimental treatments (Hou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs have become an important regulator of osteoclastogenesis, osteoblasts growth and differentiation (Chen et al, 2015;Baum and Gravallese, 2016;Liu J. et al, 2019). In experimental arthritis models, miRNAs analogs and antagonists have shown encouraging results as experimental treatments (Hou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…12 Several miRNAs, including miR-34a-3p, let-7, miR-191-5p, and miR-887-3p, have been shown to interfere with the expression of MDMX by directly binding to the 3′-UTR of MDMX mRNA. [117][118][119] Intriguingly, these miRNAs reduced the levels of MDMX protein but not MDMX mRNA. These results are not surprising given that the miRNA machinery does not frequently affect the mRNA levels but only inhibits the translation of the target genes.…”
Section: The Regulatory Effects Of Mirnas On Mdmx-p5interplaymentioning
confidence: 95%
“…It has also been found that miR-34a overexpression inhibits the growth of colorectal cancer LOVO cells and suppresses the proliferation and cell cycle progression of fibroblast-like synoviocytes (RAFLS). 118,124 In two separate cohorts of lung adenocarcinomas, a strong inverse correlation exists between miR-34 and full-length MDMX, and a considerable positive correlation occurs between miR-34 and canonical p53 targets. 124 These results suggest that the disruption of the p53-miR-34-MDMX feedback could be regarded as an important mechanism to dampen the p53-dependent tumor suppression.…”
Section: Mir-34 Familymentioning
confidence: 99%
“…Intriguingly, several miRNAs that negatively regulate inflammation or FLS proliferation are expressed at higher levels in OA synovium and FLS compared to RA, including miR-34a-3p, miR-124a, miR-30a, miR-10a, miR-140-3p, and miR-140-5p (49)(50)(51)(52)(53). MiR-34a-3p expression is decreased in RA FLS, leading to increased inflammation and proliferation (49). Downregulation of miR-34a passenger strand (miR-34a * ) in RA FLS, due to methylation of its promoter, promotes apoptosis resistance (54).…”
Section: Mirnas In Oa Synovial Pathologymentioning
confidence: 99%
“…However, it is now appreciated that OA FLS exhibit an independent miRNA signature from RA FLS ( 22 ). Intriguingly, several miRNAs that negatively regulate inflammation or FLS proliferation are expressed at higher levels in OA synovium and FLS compared to RA, including miR-34a-3p, miR-124a, miR-30a, miR-10a, miR-140-3p, and miR-140-5p ( 49 53 ). MiR-34a-3p expression is decreased in RA FLS, leading to increased inflammation and proliferation ( 49 ).…”
Section: Mirnas and Synovial Inflammation In Oamentioning
confidence: 99%